Perancangan Desain Tas Berbahan Bonggol Jagung Dengan Citra Elegan Melalui Penelusuran Aktivitas Seorang Figur - Vlavioreta Christina Hananto; Andry M; Amirul Nefo (Fakultas Industri Kreatif Universitas Surabaya, 2024)
This research involves the design of a bag using corncob material with an elegant image through the exploration of the activities of a figure, in this case, the reference figure being Maria Rahajeng. The novelty proposed in the design is the use of corncob material capable of producing an elegant image, and as a bag material, it is not widely applied in the industry, making it a distinctive feature from other bag industries, and subsequently, it can become a market opportunity for the bag product. The method used in this design is the iterative prototyping method, starting from the empathize process and ending with the test process that refers to the analysis results of the activities of a model figure. The result of this design is a prototype bag using corncob material with an elegant image, which is tested for its market absorption at a local exhibition in Bandung. This research was conducted in Bandung during a 4-month internship at PT. Matahati Kreasi Nusantara.